2016
DOI: 10.15376/biores.11.4.10240-10250
|View full text |Cite
|
Sign up to set email alerts
|

Block Shear Strength and Delamination of Cross-Laminated Timber Fabricated with Japanese Larch

Abstract: Process parameters of cross-laminated timber (CLT) fabricated with Japanese larch were evaluated. The process parameters were designed by using an orthogonal test including pressure, glue consumption, and adhesive. Both delamination and block shear tests were conducted on CLT in accordance with GB/T 26899 (2011). The results showed that the optimum process parameters were A2B3C2 including pressure (1.2 MPa), glue consumption (200 g/m 2 ), and amount of adhesive (one-component polyurethane). The weight loss and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…CLT used for prefabricated wall and floor assemblies offers many advantages, and the 'reinforcement' effect provided by the cross-lamination in Cross-Laminated Timber: A Review on Its Characteristics and an Introduction to Chinese Practices DOI: http://dx.doi.org/10.5772/intechopen.98956 residential building, with a total area of nearly 1,500 m 2 , as shown in Figure 2. CLT are used as floor, wall and roof panels of this building, and the amount of CLT used is 215 m 3 . In 2020, the first six-story pure timber structure building in China --Shandong DENCHWOOD CLT Research and Development (R&D) Center project has been completed, as shown in Figure 3.…”
Section: Introduction 11 Backgroundmentioning
confidence: 99%
“…CLT used for prefabricated wall and floor assemblies offers many advantages, and the 'reinforcement' effect provided by the cross-lamination in Cross-Laminated Timber: A Review on Its Characteristics and an Introduction to Chinese Practices DOI: http://dx.doi.org/10.5772/intechopen.98956 residential building, with a total area of nearly 1,500 m 2 , as shown in Figure 2. CLT are used as floor, wall and roof panels of this building, and the amount of CLT used is 215 m 3 . In 2020, the first six-story pure timber structure building in China --Shandong DENCHWOOD CLT Research and Development (R&D) Center project has been completed, as shown in Figure 3.…”
Section: Introduction 11 Backgroundmentioning
confidence: 99%
“…Cross-laminated timber (CLT) is a planar, large-dimension engineered timber panel, which has been used for load-bearing components including wall, floor, and roof elements in single-and multistory buildings, halls, and bridges around the world, especially in Europe, Canada, and America [1][2][3][4][5]. In recent decades, the research, production, development, application, and standardization of CLT have also been in progress in China [6].…”
Section: Introductionmentioning
confidence: 99%
“…This approach can effectively improve the rolling shear resistance of generic CLT because SCLs have been restructured and hardwood has more complex structure of growth rings, which can hinder the crack development. Chinese scholars have explored the use of domestic fast-growing species, such as larch (Gong et al 2016), eucalyptus (Liao et al 2017), poplar (Wang et al 2015), and other raw materials, to make CLT. However, it is still far from mass production and engineering applications.…”
Section: Introductionmentioning
confidence: 99%